The good women of the parish : gender and religion after the Black Death - French, Katherine L. (Middle Ages series., 2008)
French argues that medieval laywomen both coped with the chaotic changes following the plague and justified their own changing behavior by participating in local religion. Through active engagement in the parish church, the basic unit of public worship, women promoted and validated their own interests and responsibilities.